2017
DOI: 10.4041/kjod.2017.47.2.130
|View full text |Cite
|
Sign up to set email alerts
|

The combined use of computer-guided, minimally invasive, flapless corticotomy and clear aligners as a novel approach to moderate crowding: A case report

Abstract: The aim of this case report was to describe an innovative orthodontic treatment method that combined surgical and orthodontic techniques. The novel method was used to achieve a positive result in a case of moderate crowding by employing a computer-guided piezocision procedure followed by the use of clear aligners. A 23-year-old woman had a malocclusion with moderate crowding. Her periodontal indices, oral health-related quality of life (OHRQoL), and treatment time were evaluated. The treatment included interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 13 publications
0
29
0
1
Order By: Relevance
“…Reduced aesthetic impact and treatment duration are the current principal orthodontic expectations for most patients [15,27]. A corticotomy FAOT represents an ideal solution to achieve these goals [1,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced aesthetic impact and treatment duration are the current principal orthodontic expectations for most patients [15,27]. A corticotomy FAOT represents an ideal solution to achieve these goals [1,10].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, orthodontic treatment with clear aligners guarantees better periodontal health compared to fixed orthodontic appliances [30][31][32][33][34]. Despite this, oral hygiene and periodontal status should be regularly checked after surgery and throughout the period of orthodontic movements [1,27], particularly in patients that smoke [35].…”
Section: Discussionmentioning
confidence: 99%
“…24 As orthodontic clear aligners became more popular, several papers were published reporting their association with OIIRR. These papers varied between in vivo studies, 25 case reports, 26 clinical trials, 15,16 and systematic reviews. 9,17 In a study published in 2010 by Fowler, it was reported examination before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Cassetta et al described the therapy of 2 patients with moderate crowding (the 1 st with class I, the 2 nd with class II). 115,116 The treatment was completed with a satisfactory effect after 2 months (in the class I patient) and after 8 months (in the class II patient). However, attention should be paid to the low power of scientific evidence (no control group; only a case report) and the possible bias of the conducted study.…”
Section: Combined Methodsmentioning
confidence: 99%